The Uniform Data System for Medical Rehabilitation Report of Patients with Traumatic Spinal Cord Injury Discharged from Rehabilitation Programs in 2002 – 2010 - Granger, Carl V. (2012)
OBJECTIVE: Provide benchmarking information from a large national sample of patients receiving inpatient rehabilitation following a traumatic spinal cord injury. DESIGN: Analysis of secondary data from 891 inpatient medical rehabilitation facilities in the United States that contributed traumatic spinal cord injury data to the Uniform Data System for Medical Rehabilitation (UDSmr) during the period January 2002 through December 2010. Variables analyzed included demographic information (age, sex, marital status, race/ethnicity, pre-hospital living setting, discharge setting), hospitalization information (length of stay, program interruptions, payer, onset date, rehabilitation impairment group, ICD-9 codes for admitting diagnosis, comorbidities), and functional status (FIM® instrument [“FIM”] ratings at admission and discharge, FIM efficiency, FIM gain). RESULTS: The final sample included 47,153 patients with traumatic spinal cord injury. Overall mean length of stay = 26.2 (±23.2) days: yearly means ranged from 29.7 (±25.4) in 2002 to 22.9 (±18.9) in 2009. FIM total admission and discharge ratings also declined over the 8-year study period: admission decreased from 60.5 (± 17.4) to 55.9 (±16.3); discharge decreased from 86.1 (±23.8) to 82.4 (±23.4). Rehabilitation efficiency (FIM gain per day) remained relatively stable over time (1.6 ±1.7 points per day). The percentage of all patients discharged to the community ranged from 75.8% to 71.5% per year. Wheelchair users stayed in rehabilitation longer than persons who could walk (34.6 ±217.4 vs. 17.4 ±14.1 days) and also experienced less functional improvement (21.6 ±15.8 vs. 29.6 ±16.3 FIM points). CONCLUSIONS: National data from persons with traumatic spinal cord injury in 2002-2010 indicate that lengths of stay declined, but efficiency in functional independence was stable to slightly increased. Over seventy percent of patients were consistently discharged to community settings following inpatient rehabilitation.